Parent-Adolescent Relationship: Impact on Senior High School Students in the National Capital Region - Tabbada, Ghilieah Valeska G.; Rojo, Jhezrelle Lawrence D.; Badiola, Edralyn S.; Escaño, Kiana Nissi O.; Baldeo, John Vincent J.; Castillo, Kimberly Rose B. (Future Science / FSH-PH Publications, 2022)
Adolescence is a critical developmental period that requires parents and youth to renegotiate their relationships (Laursen et al., 2009). Despite being an individual who can take increasing responsibility, an adolescent still needs more protection and guidance (Sawyer, et al., 2018), therefore, the relationship with their parents is crucial. This study explored the impact of parent-adolescent relationships on the academic outcome of Senior High School students in the National Capital Region of the Philippines, focusing on 4 of its dimensions in terms of the adolescents' (a) social interaction, (b) independence, (c) self-expression, and (d) academic performance. Bodies of related literature were also reviewed to assure the reliability and accuracy of this study. Results showed that there is no significant relationship between the parent-adolescent relationship and the General Weighted Average of the students. Despite that, reviewed literature indicated that adolescents who had high levels of parent-adolescent attachment were more likely to have high levels of self-worth, which in turn enhanced their academic engagement and then improved high school grades (Chen, 2017). The researchers recommend future researchers fill the gaps this research has by conducting a study in a larger sample size to give more reliable results with greater precision and power. Future studies about the parent-adolescent relationship may focus on other dimensions aside from the four dimensions explored in this study.